New Inclinometer Device for Monitoring of Underground Displacements and Landslide Activity - Segalini, Andrea; Chiapponi, Luca; Drusa, Marian; Pastarini, Benedetta (Communications - Scientific letters of the University of Zilina, 2014)
The paper illustrates the theoretical basis of a new device called MUMS – Modular Underground Monitoring System – and one of its applications. MUMS has been designed for monitoring of underground displacements through a continuous and automated data acquisition system. MUMS instrumentation can be used to monitor the deformation of natural and artificial slopes as well as geotechnical structures. The device consists of a series of nodes located at known distances along a connecting rope and is installed within a vertical borehole. Each node measures its local rotation relative to the vertical axis by means of a 3D micro electro-mechanical acceleration sensor (MEMS). The direction cosines of each node are calculated in order to determine the 3D shape and deformation of the entire borehole. The paper illustrates an interesting application of MUMS in natural slopes and points out the benefits of the system.